PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, KEBIJAKAN DIVIDEN, LEVERAGE, KEPEMILIKAN MANAJERIAL, KEPEMILKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2016 - Ayu Wandira, 14.05.52.0057; Listiantara, G. Anggana (Students' Journal of Accounting and Banking, 2018)
This study examines the effect of profitability, company size, sales growth, dividend policy, leverage, managerial ownership, and institutional ownership on the value of the company in manufacturing companies listed on the Stock Exchange in 2012016. The population in this study were all companies listed in the Indonesian securities market in 2014 to 2016. The sample selection used purposive sampling method and obtained 113 samples. The results of this study indicate that profitability, dividend policy, and leverage have a negative and significant influence on the value of the company. While firm size, sales growth, managerial ownership, institutional ownership have a positive and significant influence on company value. Keywords: Profitability, Company Size, Sales Growth, Dividend Policy, Leverage, Managerial Ownership, Institutional Ownership And Corporate Value.